(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
It is the aim of this article to examine and analyze the air flow and velocity in the pipe when seed cotton is being transported by air. There is a discussion in the article about how seed cotton, as it moves through the pipe, affects both the air flow rate and velocity in the pipe during its passage. The investigation revealed that the air flow in the pipe is variable, thus many tests were carried out to get it to move consistently. Air flow affects the seed cotton and the pipe, reducing pressure and speed and increasing consumption.